Method of Instinbāth Law of Money Waqf Abu Hanifah Immediate Perspective - Mustafa Kamal; Hanafiyah Hanafiyah; Nainunis Nainunis; Safrizal Safrizal; Munawir Munawir; Saipul Bahri (Budapest International Research and Critics University, 2019)
This research should be done to find out how to explore and understand the contents of the text (Instinbāth pattern) of waqf legal money from the perspective of Imam Abi Hanifah. This research rests on the Instinbāth theory of Islamic law in establishing laws for the next generation. The library research uses descriptive analytical methods. The approach used in this study is referring to usul fiqh and Maqāshid al-Syāri'ah. These two approaches are used to analyze how the pattern of Instinbāth of law, as well as the constructs of the fiqh thought of Imam Abi Hanifah. From this study it can be concluded that: the pattern of istinbāth of Imam Abu Hanifah, first, in terms of coverage of nāsh from the three sources of waqf law (Q.S al-Māidah: 103, the narrative of Ibn Masūd, and the hadith of ibn 'Abbās)) dhahir lafadh al-nāsh shows the lack of encouragement of muamalah by carrying out the action of